Transformation of the structure professions in higher agricultural schools of Siberia at the end of 1950-s – beginning of 1990-s; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Petrik V. V. Valery Vladimirovich (2016, 2016)
Title screen